Designing a multi-epitope vaccine against SARS-CoV-2: an immunoinformatic approach - V. Alamdari-Palang; Z. Dehghan; M. Kian; S. Zonar; J. Fallahi; M. Sisakht; S. Khajeh; V. Razban (Инфекция и иммунитет)
Background.An outbreak of SARS-CoV-2 in 2019 has brought a great challenge to public health and rapid identification of immune epitopes for designing an effective vaccine for different variants of SARS-CoV-2 is necessary at the time of the pandemic. Rational, rapid, and precise vaccine design, especially vaccine antigen identification and optimization byin silicomethods of bioinformatics, structural biology, and immunoinformatic is critical to efficient vaccine development against the SARS-CoV-2 virus. The aim of this study was to develop a particular novel and effective vaccines vaccine using bioinformatics approaches and resources that can target B- and T-cell epitopes to combat SARS-CoV-2 infection.